Pengawasan dan Evaluasi Program Bahasa Arab untuk Peningkatan Berkelanjutan di Universitas Islam Negeri Maulana Malik Ibrahim, Malang - Razimona, Thia; Mustofa, Yusuf; Nafi'ah, Dzatu Ulum; Arifa, Zakiyah (Universitas Negeri Jakarta, 2019)
This research to find out and explain how controlling and evaluation management occur in the Intensive Program for Arabic Language at the State Islamic University (UIN) Maulana Malik Ibrahim Malang. The background of this research is due to PKPBA is the only language center that organizes Arabic language learning for all new students from all majors, which indeed requires special handling. This research uses descriptive qualitative research, and uses interview techniques, observation, and documentation in collecting data. The results showed that the controlling of a special Arabic language development program at UIN Maulana Malik Ibrahim was an internal controlling carried out by the head of program management, also included in external controlling carried out by the ministry of religion, including active controlling by looking at the program directly, and passive controlling by viewing teacher and student attendance lists, teaching journals, and other learning tools. As well as preventive and repressive controlling carried out to plan and implement the program so that it runs effectively and efficiently and controlling is also carried out after the learning activities are carried out to find out the results of the implementation of the program for further evaluation if there are deviations. While the program evaluation is conducted twice a year, this controlling and evaluation is carried out for continuous improvement which will be carried out every year for the development of the program.